Physical Quality of Mozzarella Cheese Produced by Lime Juice as an Acidifier - Purwadi Purwadi (Faculty of Animal Science Universitas Brawijaya, 2010)
ABSTRACT The research about production of Mozzarella cheese used lime juice as an acidifier was aimed to study its potency on physical quality of Mozzarella cheese. The method used in this research was experiment and designed with completely randomized design. The treatment was repeated 4 times, there were namely: K1 = 1.9 %, K2 = 2.1 %, K3 = 2.3 %, K4 = 2.5 %, K5 = 2.7 %, and K6 = 2.9 % (v/v), respectively. Variables measured were cheese yield, meltability, stretchability, and elasticity. Analysis of variance showed that the treatment didn’t give significantly difference effect (P>0.05) on cheese yield, stretchability, and elasticity. The treatment gave significantly difference effect (P<0.05) on meltability. The everage of cheese yield was 10.73 – 11.72 %, the everage of meltability was 9.18 – 10.90, stretchability 1.77 – 2.18, and elasticity 38.60 – 60.71. According to the results and discussion, the research could be concluded that the best consentration was 1.9 %. Keywords: physical quality, Mozzarella cheese, lime juice, acidifie